2012
DOI: 10.3233/jae-2012-1512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a uniform magnetic field on magnetorheological fluid under an impact load

Abstract: We carried out an impact experiment in order to investigate the influence of magnetic field intensity and inner diameter of the orifice on MR fluid motion under an impact load. The experiment was conducted by measuring the piston displacement. From the piston displacement, its velocity and acceleration were calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…They demonstrated that an MR fluid is adaptable to a wide-range of shock-loading strengths. Our previous studies investigated effects of orifice diameter, magnetic field strength [4], and chamfered orifice inlet [5] on the behavior of an MR fluid under shock loading. These studies showed that orifice diameter has a strong influence on the displacement, velocity, and acceleration of a piston, whereas magnetic field strength has a strong influence on piston displacement.…”
Section: Fig 1 An Orifice and A Tapered Metering Pinmentioning
confidence: 99%
“…They demonstrated that an MR fluid is adaptable to a wide-range of shock-loading strengths. Our previous studies investigated effects of orifice diameter, magnetic field strength [4], and chamfered orifice inlet [5] on the behavior of an MR fluid under shock loading. These studies showed that orifice diameter has a strong influence on the displacement, velocity, and acceleration of a piston, whereas magnetic field strength has a strong influence on piston displacement.…”
Section: Fig 1 An Orifice and A Tapered Metering Pinmentioning
confidence: 99%
“…[1][2][3][4] A magnetic field is a necessary condition for MRF to produce magnetorheological effect, for this reason, most of the current studies also analyze the relationship between the magnitude of magnetic field intensity and the mechanical properties and other rheological properties of MRF from the perspective of the magnetic field. [5][6][7][8][9] Instead, this article focuses on the effect of temperature, especially the effect of temperature-magnetic field coupling on the mechanics properties of MRF. Wang et al [10] used a self-developed MRF shear stress test device with temperature control function to test the rheological properties of MRF with different formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Browne et al [5] examined the performance of an MR shock absorber by conducting drop impact tests with an energy absorber. We examined the influence of the orifice diameter, the magnetic field strength, and the orifice shape on the MR fluid flow under an impact load [6,7]. These studies showed that the orifice diameter has a great effect on the displacement, velocity, and acceleration of the piston and that the magnetic field strength significantly affects the piston stroke to stop the impact mass.…”
Section: Introductionmentioning
confidence: 99%